Teoría del derecho, neoconstitucionalismo y modelo de estado constitucional en el contexto colombiano (2015)
The model of constitutional and democratic state of Law is supported by the neoconstitutionalist theory and develops individual and characteristic elements that propose innovative ideas in front of the state structure, including the constitutional supremacy, judicial review, protection and guarantee of rights and the active role of the judge as a creator of Law. In the Colombian context, it has not achieved its claims, since this model was transplanted from Europe and, therefore, social and legal reality is different; this results as negative consequences in its implementation. This article will also reflect on the theoretical proposals that have been developed as a critique of the postulates of neoconstitutionalism: popular constitutionalism, -as a theoretical proposal from the United States and the new constitutionalism that is consolidating in Latin America. These two proposals have centered around an increased activism on the part of the social sectors and the judicial review exercised by the public.